Perancangan Desain UI/UX Website SEAQIS Task Tracker untuk Mengelola Tugas Karyawan SEAQIS - Wananda, Eka Dian; Hendriyanto, Robbi; Kusuma, Guntur Prabawa (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
SEAMEO QITEP in Science (SEAQIS) has an important role in improving the competence of science educators and education personnel in Southeast Asia. Currently, project implementation in SEAQIS still uses manual methods, which results in a lack of transparency and effective control. To overcome this challenge, it is necessary to digitize the development a web-based system that can facilitate Human Resource Development (HRD), division heads, and Staf in managing, monitoring, and assessing these projects. This research aims to design the SEAQIS platform with a user experience approach using Design thinking methodology. Through this process, a high-fidelity Prototype was created and then Tested using usability testing. The Test results showed that the Prototype successfully met the user's needs, recording a usability score of 86. Thus, the designed SEAQIS Task Tracker website can improve the efficiency of SEAQIS employees' task management.